Sociodemographic profile, functionality, depression, and frailty as determinants for the risk of abuse and violence against older people in the community: An observational study conducted in Brazil. - Bruna Caroline Cassiano da Silva; Bruno Araújo da Silva Dantas; Alexandre do Amaral Maculan; Nathaly da Luz Andrade; Sandra Maria da Solidade Gomes Simões de Oliveira Torres; Carmelo Sergio Gómez Martínez; Eulália Maria Chaves Maia; Vilani Medeiros de Araújo Nunes; Maria Laurência Grou Parreirinha Gemito; Sheila Cristina Rocha-Brischiliari; Gilson de Vasconcelos Torres (PLoS ONE)
This study aimed to analyze the relationship between sociodemographic factors, health, functionality, depression, and frailty with the risk of abuse and violence against younger and older adults individuals. A cross-sectional observational study with a quantitative approach was conducted among Brazilian older adults between April and July 2022. Participants aged 60 years and older were recruited from Brazilian Primary Health Care Units. The Hwalek-Sengstock Elder Abuse Screening Test, Lawton and Brody's Instrumental Activities of Daily Living Scale, Edmonton Frail Scale, and the Geriatric Depression Scale (GDS-15) were used to assess the variables of interest. Odds Ratios (ORs) was calculated using binary logistic regression models to test the study hypothesis. The sample was divided into two groups: younger elderly individuals (aged 60-70 years) and older elderly individuals (> 70 years). A total of n = 200 individuals' participants were included in the study (n = 132 younger and n = 68 older). Non-white skin color (n = 15/ 22.1%/ p = 0.016/ OR= 2.0) was identified as a risk factor for the older group, while illiteracy emerged as a risk factor for violence in both groups (OR> 1.0). The absence of depressive symptoms and frailty were protective factors against the risk of abuse and violence in both groups (OR>1.0). Logistic regression analysis indicated that depression was the variable most strongly associated with the risk of abuse and violence, particularly in the younger group (R² = 0.46/ p < 0.001/ ß = 0.56). Among the observed associations, non-white skin color was a risk factor for abuse and violence in the older group, whereas literacy, absence of depression, and absence of frailty were protective factors in both groups.